2016
DOI: 10.1128/mbio.01824-16
|View full text |Cite
|
Sign up to set email alerts
|

Networked Chemoreceptors Benefit Bacterial Chemotaxis Performance

Abstract: Motile bacteria use large receptor arrays to detect and follow chemical gradients in their environment. Extended receptor arrays, composed of networked signaling complexes, promote cooperative stimulus control of their associated signaling kinases. Here, we used structural lesions at the communication interface between core complexes to create an Escherichia coli strain with functional but dispersed signaling complexes. This strain allowed us to directly study how networking of signaling complexes affects chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 54 publications
5
51
0
Order By: Relevance
“…Results from "Imposed" simulations supported previous findings indicating that the ECP behavior is governed by receptor sensitivity rather than absolute attractant concentration [28,54]. Similarly, more recent biochemical work [55] has also substantiated the long-held notion that the networked architecture of chemosensory receptor arrays in E. coli plays a vital role in the cell's robust response behavior. Results of simulations that incorporate CLB-ADT emphasize the importance of advective-diffusive transport phenomena in modeling ECP trajectories in fluidic environments.…”
Section: Discussionsupporting
confidence: 73%
“…Results from "Imposed" simulations supported previous findings indicating that the ECP behavior is governed by receptor sensitivity rather than absolute attractant concentration [28,54]. Similarly, more recent biochemical work [55] has also substantiated the long-held notion that the networked architecture of chemosensory receptor arrays in E. coli plays a vital role in the cell's robust response behavior. Results of simulations that incorporate CLB-ADT emphasize the importance of advective-diffusive transport phenomena in modeling ECP trajectories in fluidic environments.…”
Section: Discussionsupporting
confidence: 73%
“…In fact, it has been previously shown that a strain, where FrzCD molecules can no longer bind DNA and are, thus, diffused (Figure 1) can still produce reversals (Bustamante et al, 2004). In E. coli chemosensory cluster formation is also not critical for signal transduction but it confers properties such as the amplification of signal, a direct consequence of the cooperative interactions between clustered chemoreceptors [1115]. Thus, we decided to check if the formation of DNA-bound Frz clusters can also promote cooperativity in the signaling activity of the Frz chemosensory system.…”
Section: Resultsmentioning
confidence: 99%
“…Receptor clustering is not strictly required for signal transduction, as one functional unit is enough to generate phosphorylated CheY [6,911]. However, MCP clustering is essential to ensure the amplification of the initial signal, which is a direct consequence of the cooperative interactions between clustered chemoreceptors [1115].…”
Section: Introductionmentioning
confidence: 99%
“…The networking of signaling complexes in extended arrays leads to a cooperative response with enhanced sensitivity and dynamic range (20, 32, 39, 40), ultimately resulting in robust chemotactic performance (41). However, our understanding of how receptors collaboratively control kinase activity within an array is limited.…”
Section: Figmentioning
confidence: 99%